The Factor Structure, Internal Consistency, and Convergent Validity of Two Suicide Assessment Competency Measures in Vocational Rehabilitation Counselors. (October 2017) - Lund, Emily M.; Schultz, Jared C.; Nadorff, Michael R.
We analyzed the psychometric properties of two published self-report suicide assessment competency rating scales—the Suicide Competency Inventory (SCI) and the Suicide Competency Assessment Form (SCAF)—in a multistate sample of 223 public-sector vocational rehabilitation counselors. Both measures demonstrated very good to excellent internal consistency in our sample. Exploratory factor analysis indicated the SCI loads on a three-factor model whereas the SCAF loads on a single factor; these are consistent with the theoretical scale structures proposed by the original authors of the scales. In addition, both scales were highly correlated with each other, providing strong initial evidence of construct validity. In sum, our results support the use of these measures as a reliable and valid means of assessing perceived suicide assessment competency in rehabilitation counselors.